2013
DOI: 10.1021/ma4006846
|View full text |Cite
|
Sign up to set email alerts
|

Sticky Supramolecular Grafts Stretch Single Polymer Chains

Abstract: The folding of single polymeric chains into single chain polymeric nanoparticles (SCPNs) is a unique strategy to prepare ordered structures at the nanoscopic level. Structure forming elements are attached to a polymer chain designed to fold it into a well-defined object, the SCPN. The self-assembly of these units has been investigated in great detail. However, little is known about the impact of the resulting secondary structure on the conformation of the polymer chain. Here we employ a combination of scatteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
103
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(107 citation statements)
references
References 52 publications
4
103
0
Order By: Relevance
“…Supramolecular folding of polymer chains into single chain polymeric nanoparticles (SCPNs) is an attractive alternative to prepare compartmentalized, water-soluble, nanometersized particles with a hydrophobic interior. [29][30][31][32] Notably, the benzene-1,3,5-tricarboxamide (BTA) is an attractive unit to form SCPNs with well-defined, conformationally adaptable, three-dimensional structures as a result of the hydrogenbond-driven, helical self-assembly of the BTA units. 31 Detailed scattering studies revealed that water-soluble copolymers based on oligo(ethylene glycol) methacrylate (oEGMA) and benzene-1,3,5-tricarboxamide methacrylate (BTAMA) fold in water into compact conformations Additional Supporting Information may be found in the online version of this article.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supramolecular folding of polymer chains into single chain polymeric nanoparticles (SCPNs) is an attractive alternative to prepare compartmentalized, water-soluble, nanometersized particles with a hydrophobic interior. [29][30][31][32] Notably, the benzene-1,3,5-tricarboxamide (BTA) is an attractive unit to form SCPNs with well-defined, conformationally adaptable, three-dimensional structures as a result of the hydrogenbond-driven, helical self-assembly of the BTA units. 31 Detailed scattering studies revealed that water-soluble copolymers based on oligo(ethylene glycol) methacrylate (oEGMA) and benzene-1,3,5-tricarboxamide methacrylate (BTAMA) fold in water into compact conformations Additional Supporting Information may be found in the online version of this article.…”
Section: Introductionmentioning
confidence: 99%
“…consisting of a single polymer chain, and having a slightly elongated shape as a result of the BTA self-assembly. 29 We recently inserted catalytically active moieties into BTAbased amphiphilic copolymers. 31,33 A set of random amphiphilic copolymers comprising oEGMA/BTAMA and L-proline units was prepared via reversible addition-fragmentation chain transfer (RAFT) polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Meijer and coworkers also expanded the scope of possible architectures by successfully synthesizing SCNP from cylindrical brush block polymers as well as an orthogonally collapsible ABA triblock copolymer [6,22]. Additionally, this group studied temperature and co-solvent induced changes in the secondary structures of benzene-1,3,5-tricarboxamides (BTA)-based SCNPs, and developed a compartmentalized metal ion SCNP sensor that shows impressive binding affinities [4,23]. The Barner-Kowollik group demonstrated a photo-induced Diels-Alder ligation to create SCNP in addition to using metal-ligand complexation to induce controlled folding by linking chain ends [1,24].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] SCNPs based on self-collapsed individual chains mimic the structure of folded biomacromolecules although in a rough, primitive manner. [7][8][9][10][11][12][13][14] Recently, we have demonstrated a very efficient strategy for the construction of transient binding disordered protein-mimic nano-objects based on SCNPs. 15 Small angle neutron scattering (SANS) and molecular dynamics (MD) simulation results undoubtedly showed that the form factor of these SCNPs in solution resembles that of intrinsically disordered proteins (IDPs).…”
mentioning
confidence: 99%